Geoinformation techniques to estimate water balance in eucalyptus - Facco, Alexandro Gomes; Ribeiro, Aristides; Pruski, Fernando Falco; Monteiro, Welliam Chaves; Leite, Fernando Palha; Andrade, Ricardo Guimarães; Menezes, Sady Júnior Martins da Costa de (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the influence of topography on radiation balance and water availability in micro watersheds planted with eucalyptus, and to verify the effects of eucalyptus plantations in regulating water flow. Water balance components were monitored in a micro watershed located in the Eastern region of the state of Minas Gerais, Brazil. Water balance components were computed punctually and spatially, in hourly time scale, for the useful layer of soil. The results were compared with the values measured from the water depth drained by the watercourse. In months with soil water availability, the average values of real transpiration estimated by the spatial method were higher than those estimated by the punctual method. Water balance estimation is more efficient when it considers the relief effects. Eucalyptus forests regulate water flow in micro watersheds.
Keywords: soil water storage; experimental micro watershed; water flow regulation; relief; geographic information system.